Planning and implementing electronic records management : a practical guide - Smith, Kelvin (Kelvin John) (London : Facet Pub., 2007)
This book provides straightforward, practical guidance on how to prepare for and enable ERM. It sets out and explains the issues organizations need to consider in selecting a system, and the procedures required for effective implementation. Help is also given with the complexities of managing hybrid records during an interim period between paper and electronic record management.The book is divided into three main parts covering the preparation for ERM, and its design and implementation.
Includes index.
oif 17/06/14
Loan
Keywords: Electronic records -- Management; Electronic filing systems; Business records -- Data processing -- Management; Records -- Data processing -- Management